Violence and Corruption of Megachurch Leaders: Unravelling Silent Coloniality in Zimbabwe - Dube, Bekithemba (Religions, 2023)
This theoretical article argues that megachurches are an inadequately problematised factor in the Zimbabwean crisis and uses, as examples of violent and corrupt megachurch leaders, Emmanuel Makandiwa, Uebert Angel, and Passion Java. As Zimbabwe moves towards elections in 2023, ZANU-PF has resorted to using megachurches to enact propaganda, create voter empathy, and stir up violence, dividing the religious electorate along party lines in the process. The article is couched in decoloniality theory to position megachurch leaders within instability and as thwarting democracy in Zimbabwe. I respond to two questions: how do Makandiwa, Angel, and Java contribute to thwarting democracy while promoting corruption and violence? And, how can religion be approached from the perspective of decolonial thinking to reverse the crisis that has been created by prophets in Zimbabwe? I end by arguing that the Zimbabwean crisis takes various forms and that the role of megachurch leaders in finding a solution and in reconstructing narratives of peace and good governance in Zimbabwe cannot be ignored.